The effects of football practice on children's fundamental movement skills: A systematic review and meta-analysis - Xiaojin Mao; Jingyue Zhang; Yulian Li; Yuang Cao; Meng Ding; Weidong Li; Lixia Fan (Frontiers Media S.A., 2022)
The purpose of this systematic review and meta-analysis was to explore the effects of different soccer practices on fundamental movement skills (FMS) of children of different ages and genders, in order to help children to improve their fundamental movement skills through soccer practice more effectively. The databases of CNKI, Wanfang database, Pubmed, Web of science and Cochrane library were searched to collect relevant studies on the effects of soccer practices on FMS, and the quality of the included studies was evaluated by using the Cochrane Risk of Bias Tool, and Meta-analysis was conducted by Review Manager 5.4 software. 16 studies were finally included, with a total of 3,121 subjects were included. The results showed that soccer had a positive effect on linear sprint ability [SMD 95% CI = −0.37 (−0.61, −0.14), P = 0.002], horizontal jump [SMD 95% CI = 0.22 (−0.34, 0.77), P = 0.003], object control [SMD 95% CI = 1.32 (0.8, 1.85), P = 0.0003], Closed-eye single-leg test [SMD 95% CI = 0.87(0.48,1.25), P < 0.0001],while countermovement jump [SMD 95% CI = 0.50(−0.35,1.35), P = 0.25] and flamingo balance [SMD 95% CI = −0.16(−0.31,−0.02), P = 0.03] had a less significant effect. Meanwhile, the effect of the practice was mainly influenced by the total duration of the intervention, age and gender of the intervention subjects, in which the total intervention time longer than 1,800 min promoted linear sprint ability, horizontal jump and flamingo balance test better than those below 1,800 min; the promotion effect of linear sprint ability and horizontal jump was better in children aged 7-9 years than 10-13 years, while Children aged 10-13 years showed better improvement in Closed-eye single-leg test after the intervention than 7-9 years; Girls were better promoted in linear sprint ability and Closed-eye single-leg test, but the horizontal jump is better for boys to improve the effect. It is recommended that the effects of different soccer practice contents on fundamental movement skills can be further explored in the future to improve the relevance and efficiency of fundamental movement skill development for children.